Cooperative coordination-mediated multi-component self-assembly of "all-in-one" nanospike theranostic nano-platform for MRI-guided synergistic therapy against breast cancer - Xiaojie Chen; Xudong Fan; Yue Zhang; Yinghui Wei; Hangsheng Zheng; Dandan Bao; Hengwu Xu; Ji-Gang Piao; Fanzhu Li; Hongyue Zheng (Elsevier, 2022)
Carrier-free multi-component self-assembled nano-systems have attracted widespread attention owing to their easy preparation, high drug-loading efficiency, and excellent therapeutic efficacy. Herein, MnAs-ICG nanospike was generated by self-assembly of indocyanine green (ICG), manganese ions (Mn2+), and arsenate (AsO43−) based on electrostatic and coordination interactions, effectively integrating the bimodal imaging ability of magnetic resonance imaging (MRI) and fluorescence (FL) imaging-guided synergistic therapy of photothermal/chemo/chemodynamic therapy within an "all-in-one" theranostic nano-platform. The as-prepared MnAs-ICG nanospike had a uniform size, well-defined nanospike morphology, and impressive loading capacities. The MnAs-ICG nanospike exhibited sensitive responsiveness to the acidic tumor microenvironment with morphological transformation and dimensional variability, enabling deep penetration into tumor tissue and on-demand release of functional therapeutic components. In vitro and in vivo results revealed that MnAs-ICG nanospike showed synergistic tumor-killing effect, prolonged blood circulation and increased tumor accumulation compared to their individual components, effectively resulting in synergistic therapy of photothermal/chemo/chemodynamic therapy with excellent anti-tumor effect. Taken together, this new strategy might hold great promise for rationally engineering multifunctional theranostic nano-platforms for breast cancer treatment.